2012
DOI: 10.1299/jtst.7.135
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on a Compact Methanol Steam Reformer with Pd/Ag Membrane

Abstract: The performance of high purity hydrogen production from methanol for a compact steam reformer with a hydrogen purification membrane was investigated experimentally. A 77 wt.% Pd/23 wt.% Ag membrane with 25µm thickness and CuO/ZnO/ Al 2 O 3 catalyst were used. Heating was performed by a Bunsen type burner using City Gas 13A. The methanol reforming and purification of H 2 were investigated at different reference catalyst zone temperatures (589-689K), pressures at the retentate side (0.2-0.5MPa), steam to methano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The estimation by the equation for the case of hydrogen mixture is quantitatively reconsidered by taking into account the hydrogen concentration decrease at the membrane surface of the upstream side due to permeation. This is a continuation of previous study (22) , which just described the equation predicted the trend of H 2 permeation flux qualitatively. The proposed estimation method is supposed to be practically useful for the permeation system with similar geometry, in which the similar geometry has been implemented for many applications (22)- (25) .…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…The estimation by the equation for the case of hydrogen mixture is quantitatively reconsidered by taking into account the hydrogen concentration decrease at the membrane surface of the upstream side due to permeation. This is a continuation of previous study (22) , which just described the equation predicted the trend of H 2 permeation flux qualitatively. The proposed estimation method is supposed to be practically useful for the permeation system with similar geometry, in which the similar geometry has been implemented for many applications (22)- (25) .…”
Section: Introductionsupporting
confidence: 85%
“…In this experiment, the gas mixture of hydrogen and nitrogen with a constant hydrogen mole fraction of 0.75 was used for all conditions. This mole fraction was selected based on the overall methanol steam reforming reaction model, as demonstrated in our previous study (22) .…”
Section: Experimental Methods and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In this experiment, the gas mixture of hydrogen and carbon dioxide with constant inlet H 2 mole fraction of 0.75 was used. This fraction was selected based on the overall methanol steam reforming reaction model, as mentioned in our previous study [10]. A flat sheet, dense 77wt.% Pd/23wt.% Ag purification membrane with a thickness of 25µm and diameter of 0.02m was set inside the test module.…”
Section: Experimental Setup and Conditionsmentioning
confidence: 99%
“…Besides the CO remover using the chemical reaction, a methanol steam reformer with Pd/Ag membrane was proposed as a method of hydrogen purification. Faizal et al(2012) elucidated the importance of transport phenomena near the membrane for relatively low flow rate of reformed gas and proposed a quantitative estimation method of H 2 purification flow rate from reformed gas. It showed that the Pd/Ag membrane is useful for compact reformer to produce high purity hydrogen with very low CO concentration, which fulfills the PEFC requirement.…”
Section: Introductionmentioning
confidence: 99%